Exploring theoretical engagement in empirical tour guiding research and scholarship 1980–2016: a critical review. Issue 1 (1st January 2019) - Black, Rosemary; Weiler, Betty; Chen, Hanyu
ABSTRACT: This paper critically reviews the theoretical engagement of empirically-based tour guiding literature published in the tourism literature from 1980 to 2016, as a driver for future high-quality, rigorous research. An analysis of 140 empirical studies on tour guides and tour guiding during this period provides a foundation for identifying patterns, trends and gaps in relation to theory engagement. Engagement with theory has increased, particularly since 2010, however the trend is not consistent across variables such as study location and type/genre of tour guiding. The geographical location of tour guiding research is uneven with research predominantly undertaken in Western countries and Asia. A third of all empirically-based tour guiding journal papers were published in four high ranking, high impact tourism journals, and engagement with theory was generally greater for those studies published in high-ranked journals. An important finding is that theory is being used by tour guiding scholars to inform their research, but the testing, refinement and building of new theory is limited. A model depicting five key relationships that have been studied using theory in the tour guiding literature is presented. This model assists in identifying research gaps and opportunities for future research in this field of study.